2020
DOI: 10.5658/wood.2020.48.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Color Change and Resistance to Subterranean Termite Attack of Mangium (Acacia mangium) and Sengon (Falcataria moluccana) Smoked Wood

Abstract: Indonesian log production is dominated by young trees harvested from plantation forests. The timber contains of sapwood and juvenile wood, which are not resistant to termite attack. Smoking treatment can enhance wood resistance to termite attack, but it also changes the color. Specimens of mangium (Acacia mangium) and sengon (Falcataria moluccana) wood were exposed for 1, 2, and 3 weeks to smoke produced from the pyrolysis of salam (Syzygium polyanthum) wood. The color change of the wood was measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In summary, there was a significant difference in color (ΔE) between the untreated wood samples (control) and wood samples impregnated with catechin solutions. This finding is relevant to the study by Hadi et al (2020Hadi et al ( , 2022, who reported that any chemical treatment of wood could potentially change its natural color. However, no color differences were observed among the wood samples treated with catechin solutions at concentrations of 9%, 12%, and 15%.…”
Section: Discoloration After Exposure To the Stain Fungisupporting
confidence: 51%
“…In summary, there was a significant difference in color (ΔE) between the untreated wood samples (control) and wood samples impregnated with catechin solutions. This finding is relevant to the study by Hadi et al (2020Hadi et al ( , 2022, who reported that any chemical treatment of wood could potentially change its natural color. However, no color differences were observed among the wood samples treated with catechin solutions at concentrations of 9%, 12%, and 15%.…”
Section: Discoloration After Exposure To the Stain Fungisupporting
confidence: 51%
“…9 showed that jabon wood and rubberwood were most favored by termites during the baiting, followed by pine, manii, IV due to its low resistance to subterranean termites (Arsyad et al, 2019). Acacia was classified as resistance class III and for sengon wood was class V (Hadi et al, 2020). The class also indicates that the wood species was favored by termites and caused greater damage.…”
Section: Percentage Of Wood Damagementioning
confidence: 99%
“…The results indicated the use of hot pressing at 200 ˚C tended to produce a darker colour on the specimen surface than at the temperature of 180 ˚C. The discoloration of the smoked-wood specimens, where they appeared darker and stronger compared to the non-smoked specimens occurred due to heat exposure during the wood-smoking process (Hadi et al 2020). Such discoloration of the thermally compressed specimens was due to the presence of the heat-stable or the least degraded lignin.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 93%